1995
DOI: 10.1002/1097-0142(19950215)75:4<973::aid-cncr2820750412>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of bone. Correlation of magnetic resonance imaging features with cytokine production by tumor cells

Abstract: Background. Primary lymphoma of bone is a rare, aggressive neoplasm that can present with a large, soft‐tissue mass despite minimal evidence of cortical destruction on plain radiographs. Methods. High resolution magnetic resonance imaging (MRI) examinations of four patients with primary lymphoma of bone were reviewed retrospectively, and in each case intramedullary tumors demonstrated “penetrating channels” extending through the cortex. The MRI studies were correlated with the histopathologic assessment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 39 publications
2
35
0
1
Order By: Relevance
“…Interestingly, the pattern of extensive marrow disease and surrounding soft-tissue masses but without extensive cortical destruction has been reported nearly exclusively in round cell tumors such as primary bone lymphoma, multiple myeloma, and Ewing sarcoma (Fig 11c) (1,21). One explanation for this finding is the spread of tumor cells from the marrow through small vascular channels that run through the cortex into the surrounding soft tissue (22).…”
Section: Soft-tissue Involvementmentioning
confidence: 99%
“…Interestingly, the pattern of extensive marrow disease and surrounding soft-tissue masses but without extensive cortical destruction has been reported nearly exclusively in round cell tumors such as primary bone lymphoma, multiple myeloma, and Ewing sarcoma (Fig 11c) (1,21). One explanation for this finding is the spread of tumor cells from the marrow through small vascular channels that run through the cortex into the surrounding soft tissue (22).…”
Section: Soft-tissue Involvementmentioning
confidence: 99%
“…The mechanism by which PBL traverses an apparently intact cortex is through cortical tunnelling, which was demonstrated by Hicks et al 18 In that study, MRI, histopathological and immunohistochemical correlation revealed cutting cones with marked osteoclastic activity and extensive bone resorption in the form of narrow channels through cortical bone, which were filled with tumour cells.…”
Section: Discussionmentioning
confidence: 75%
“…The difference in these cytokine profile patterns is thought to influence the laboratory findings. In BMN, these cytokines and chemokines may be produced by systemic ALL cells and accessory cells, as described previously [10]; however, the possibility that massive cell death induced these responses, especially in the release of inflammatory cytokines such as TNF-α, IL-1β, and IL-6, could not be excluded. Additionally, we examined the levels of HMGB1, which was originally characterized as a non-histone, nuclear DNA-binding protein [11,12].…”
Section: Discussionmentioning
confidence: 99%